Effectiveness of online learning: a multi-complementary approach research with responses from the COVID-19 pandemic period - Batdi, Veli; Dogan, Yunus; Talan, Tarik (Routledge Journals, Taylor & Francis Ltd, 2023)
While there has been an upsurge in transition to online learning taking place mostly in higher education, many countries around the world have had to leave their brick-and-mortar schools all of a sudden and necessarily turn to fully-online education since the outbreak of Coronavirus pandemic (Covid-19). Such global emergency cases reacquaint us with the fact that education cannot be taken for granted, making the findings of the current research literature inevitable and ready for immediate use for future policy-making regarding online education. Thus, we planned to conduct the present research synthesis including more recent empirical studies of both a quantitative and qualitative character. We took a multi-complementary approach including a meta-analysis together with a meta-thematic analysis of the effectiveness of online education. In order to further complement and consolidate the results of these two reviews of previous studies, we conducted a mixed-methods research (a pre-experimental study and a qualitative study) designed specifically to understand the responses from the abrupt transition period of online education. This kind of research approach is believed to make more contributions to the relevant literature as it may provide a more in-depth perusal of the impacts of online learning on and its effectiveness in student achievement.
Keywords: Online learning; achievement; meta-analysis; thematic analysis; Covid-19